EFEKTIVITAS E-PORTOFOLIO VIDEO UNTUK MENINGKATKAN SKILL DAN MOTIVASI PESERTA DIDIK PADA MATA PELAJARAN DESAIN GRAFIS PERCETAKAN DI SMK KARTIKA XX-I MAKASSAR - Novitasari; Darlan Sidik; Riana T. Mangesa (UNM Journal of Technology and Vocational, 2022)
The purpose of the study was to see the effectiveness of the video e-portfolio to improve the skills and motivation of students in printing graphic design lessons. Assessment is an important subsystem in education. Indicates the need for innovation in accordance with the development of science and technology. E-Portfolio is software to present students' mastery and skills effectively, because it can store materials, images, audio and video. This type of research is experimental research. This research method is a pre- experimental design using the one group pretest-posttest design. Data collection techniques using questionnaires were given to students and teachers, with this questionnaire the authors obtained data about skills, student motivation and teacher responses. The research sample for class XI multimedia was 20 people. The results showed that there was an increase in skills in the field of photography, the percentage of the average value of the pre test was 43.36% and the post test was 85.45% from the ideal score of 100. Data analysis used the T-test to see the completeness of student learning before and after being taught to make e-portfolios. videos. The classical mean value of learning outcomes before treatment was 15% and after treatment was 90%, with a significance value (Sig) <0.05. The percentage of students' responses was 91% very good category. Student motivation with a percentage of 76.14% in good category. While the teacher's response has a percentage of 96% indicating that the teacher gave a very good response to the video e-portfolio assessment for use in the assessment of printing graphic design subjects. Keywords: Photoshoot skills, work motivation, E-portfolio Video, Graphic Design